EUCALYPTUS ‘GG 100’ RESPONSE TO SIMULATED DRIFT OF ORTHOSULFAMURON - Tardeli, Mayara Jade do Nascimento; Bidóia, Vitor Simionato; Cesarin, Anne Elise; Alves, Pedro Luis da Costa Aguiar (Floresta, 2024)
Plant growth regulators and low doses of herbicides are used in some crops in order to achieve satisfactory yields. They can cause morphological or physiological changes in plants qualitatively or quantitatively, such as in the inhibition and delay of vegetative development, in the early maturation or in sugar accumulation. The application of these products through spraying aims to reach the target crop. However, some neighboring crops may be contaminated through drift. The present study aims to evaluate the effects of simulated drift of orthosulfamuron on the initial growth of Eucalyptus urophylla seedlings, clone GG 100. The experiment was installed in pots of 5 L capacity in a completely randomized design, with nine treatments and four replicates. The treatments consisted of the following nine increasing doses of orthosulfamuron ripener: 0; 1.19; 2.39; 4.78; 9.56; 19.12; 38.25; 76.5; and 127.5 g a.i. ha-1. The height of the eucalyptus plants were evaluated at 0, 14, 28, 42, and 63 days after application (DAA). At 63 DAA, in the end of the experiment, the stem diameter, leaf area, and the dry matter of leaves, stems, and roots were evaluated. In conclusion, there were no deleterious effects of the drift of orthosulfamuron up to the dose of 127.5 g a.i. ha-1 on the development and growth of E.urophylla seedlings, clone GG 100, up to 63 days after application.